Pengembangan Modul Pembelajaran Berbasis Website Pada Sistem Informasi Pendaftaran Peserta Didik Baru (PPDB) di SMP Negeri 2 Tamanan Bondowoso - Hidayah, Nurul; Wahyudi, Rifan Indra; Prawira, Bagus Yuda (Universitas Bakti Indonesia, 2024)
This research was conducted to develop the New Student Acceptance Application (PPDB) with an online system. This is based on Karen at SMP Negeri 2 Tamanan still using a manual system. The method used, namely SDLC, begins with system analysis and design, design, web coding, testing, implementation, maintenance. The results of the study show that this application makes it easier for participants to register online.